KerepekScape / Ammar Mohd Abdul Nassir and Muhammad Aiman Nur Hakeem Norjorizwan - Mohd Abdul Nassir, Ammar; Norjorizwan, Muhammad Aiman Nur Hakeem (2022)
KerepekScape is a new company established in Malaysia. The name has been taken from the combination of “Kerepek” a kind of snack that is cut thin and fried until crisp and “Escape” from emotional problems and troubling thoughts. KerepekScape is a partnership-owned online business by, Muhammad Aiman Nurhakeem Bin Norjorizwan and Ammar Bin Mohd Abdul Nassir. The company’s main goal is to provide a wide variety of food products mainly of the "Kerepek" variety to our customers at reasonable prices and with luxurious flavors that they will remember for the rest of their lives. To be precise, the business journey started in the month of June this year, 2022. The purpose of this social media portfolio is to see students' creativity and ideas for setting up a business and creating an interesting post that will attract customers. This will enable students to generate more ideas and apply their online business experience in the future. Furthermore, this task allows students to discover how businesses operate online, particularly the timing of posts and the content that is relevant or not to post on social media. Because social media users are increasing every day in this technological era, it is a great way for us to promote our product. We can increase our sales with zero cost by using social media. It was certainly not adaptable to the new features, but it is interesting to explore and learn. The time span for reaching out to our customers in regards to our launching, promotion, and awareness has also become much faster and easier compared to the old-fashioned banner or advertisement in the newspaper, which people nowadays are less likely to come across. That is why KerepekScape takes advantage of this opportunity to sell a variety of food products on this platform, as it will increase our sales and make it easier for customers to reach our products, allowing us to profit. To attract customers, we utilize a variety of selling techniques such as teaser, soft sell, and hard sell. KerepekScape fully utilizes the Facebook platform as well as WhatsApp free online communication application in terms of updating frequently to give a sense of activity to people who come across the page, communicates with customers by accepting multiple inquiries and requests and taking customer orders. Since Facebook is a large platform where it's very conducive to online businesses, KerepekScape uses this opportunity as a way to expose the product's visibility to the public in order to attract dozens of new customers, therefore resulting in a large sum of sales.